The Distribution of Obligatory Bequest to Non-Muslim Biological Children from the Perspective of Islamic Inheritance Law in Indonesia - Kutaraya, Mura Kan; Hamidah , Siti; Chanifah, Nur (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study evaluates the application of the Compilation of Islamic Law in Indonesia (KHI) in the Supreme Court Decision Number 721/K/Ag/2015, which awarded half of the deceased's inheritance to the plaintiff, who had been married to the deceased under a false identity for seventeen years. Controversy arose from the religious differences of the deceased, who was declared Muslim, and the Christian burial process, raising questions about the validity of the marriage. Using a normative juridical research method, including statutory and analytical approaches, this analysis investigates the court's disregard of the KHI, despite its recognized authority within the Indonesian legal context, particularly in inheritance and bequest disputes. The research findings indicate that the court's reliance on the interpretation by Yusuf Al-Qardhawi instead of the KHI diminishes legal certainty. The study concludes that for better judicial consistency and fairness in inheritance cases, explicit consideration of the KHI is essential. This insight underscores the need for judicial adherence to established legal norms to maintain integrity and predictability in legal proceedings, which has significant implications for the legal community's approach to similar cases.